Internalization of Cultural and Religious Values in Banten Lama Area in Social Studies Learning in Elementary Schools - Supriatna, Encep; Alfarisa, Fitri; Susilawati, Susilawati; Ridwan, Ita Rustiati (Universitas Pendidikan Indonesia, 2020)
This research was motivated by the anxiety felt by parents and teachers at the educational process that only relies on the cognitive aspects, ignoring the affective aspects, so that it makes learning less meaningful, so that learning is meaningful, the material is not foreign to students, therefore social studies material can be taken from sources closest to students. One of the contextual learning can help students understand the various sources of learning from the student's socio-cultural environment, the teacher can start it by looking for socio-cultural values that are relevant to the themes of social studies learning. For this reason, the researcher tries to use the socio-cultural environment of students in this case the Banten Lama area as a source of learning in elementary schools so that it is hoped that children will follow and identify themselves according to the stories in the learning. The location of the primary school which is the subject of this study is the SD Laboratory of the UPI Serang Campus which is located in the city of Serang. The research method uses a qualitative research approach with the phenomenological method then the results of the research are used as teaching material in social studies learning in elementary schools by conducting a series of cycles starting from planning, implementation, observation and reflection. While the data analysis is done by means of triangulation, member check, trial audit and expert opinion, then the data that has been analyzed draw conclusions.